Reconstruction of auricular conchal defects with local flaps. Issue 46 (November 2016) - Zhu, Ji; Zhao, Hui; Wu, Kai; Lv, Chuan; Bi, Hong-da; Sun, Meng-yan; Wang, Yu-chong; Xing, Xin; Xue, Chun-yu
Abstract : Abstract: Reconstruction of the auricular conchal cavity is relatively difficult because of its unique structure, shape, and location. We compared different methods of repair of the auricular concha to determine the method that would cause the least injury to the donor site. The method selected was based on the location and size of the defect. If the defect was located in the upper part of the concha, or if the defect was >15 mm in diameter, we used a post-auricular subcutaneous pedicle island flap that was pulled through a post-auricular sulcus tunnel to cover the wound. If the defect was located in the lower part of the concha and was <15 mm in diameter, we used a pre-auricular translocation flap that was passed through the intertragic notch to cover the wound. The donor site was closed primarily. All flaps survived well and any scars associated with the surgery were unnoticeable. No tumor relapse or metastasis was observed over a mean follow-up period of 35 months. All patients were satisfied with the outcome. The periauricular flap technique chosen for reconstruction of skin defects in the auricular concha depends on the size and location of the defect. With appropriate flap selection, excellent functional, and aesthetic outcomes are achieved.